2012
DOI: 10.1021/jf204451n
|View full text |Cite
|
Sign up to set email alerts
|

Apo-8′-lycopenal Induces Expression of HO-1 and NQO-1 via the ERK/p38-Nrf2-ARE Pathway in Human HepG2 Cells

Abstract: Lycopene and its metabolite apo-10'-lycopenoic acid have been shown to induce phase II detoxifying/antioxidant enzymes through activation of the nuclear factor erythroid-derived 2-like 2 (Nrf2)-antioxidant response element (ARE) transcription system. However, little is known about whether apo-8'-lyocpenal, one of the main metabolites of lycopene in rat livers, in lycopene-containing food, and in human plasma, has similar effects. This study investigated the effect of apo-8'-lycopenal on Nrf2-ARE system-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…Thus, this pattern suggests that lycopene cleavage metabolites produced by BCO2 may have anti-prostate-cancer bioactivity and that their production is diminished in the Bco2−/− mice. Previous studies on the effect of the lycopene metabolite, apo-10’-lycopenoic acid, have shown it to reduce hepatic inflammation, steatosis, and tumorigenesis in mice (60, 61), and other studies of apo-8’-lycopenal in models of liver cancer have been indicative of bioactivity (38, 39), increasing the plausibility of lycopene metabolite activity in the prostate. We also demonstrate that tomato-fed Bco2−/− accumulate lycopene precursors, phytofluene, zeta-carotene, and a suggestion for phytoene, opening the door for hypotheses regarding the potential for BCO2 to cleave additional carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this pattern suggests that lycopene cleavage metabolites produced by BCO2 may have anti-prostate-cancer bioactivity and that their production is diminished in the Bco2−/− mice. Previous studies on the effect of the lycopene metabolite, apo-10’-lycopenoic acid, have shown it to reduce hepatic inflammation, steatosis, and tumorigenesis in mice (60, 61), and other studies of apo-8’-lycopenal in models of liver cancer have been indicative of bioactivity (38, 39), increasing the plausibility of lycopene metabolite activity in the prostate. We also demonstrate that tomato-fed Bco2−/− accumulate lycopene precursors, phytofluene, zeta-carotene, and a suggestion for phytoene, opening the door for hypotheses regarding the potential for BCO2 to cleave additional carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of polyphenols in PB such as chavicol or euginol inducing Nrf2 was also reported by a study of Tsai et al, who showed that phenolic compounds from rosemary and carnosic acid induced transcription of Nrf2, ARE luciferase reporter activity and increased expression of NQO1 gene and protein in rat clone 9 cells [41]. Lycopene metabolite, apo-8’-lycopenal that can be found in rat liver and human plasma after consuming lycopene-containing food, induced nuclear translocation, Nrf2-ARE binding activity, HO-1 and NQO1 genes and proteins expression in human hepatoma cell lines, HepG2 [42]. The isothiocyanate, sulforaphane and the flavonoid, epigenin increased gene expression of phase II detoxifying enzyme such as glutathione S-transferase (GSTA1) and UDP-glucuronosyltransferase (UGT1A1) in human colon adenocarcinoma [43].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table , ERK can be phosphorylated by fruit and vegetable constituents, such as quercetin, sulforaphane/PEITC, diallyl sulfide, hydroxytyrosol, resveratrol, lycopene, luteolin, procyanidin B2, anthocyanins, hesperidin, and ferulic acid; by herb constituents, such as α‐iso‐cubebenol, schisandrin B, oleanolic acid, eupatilin, Aralia continentalis extract, rottlerin, acteoside, tanshinone IIA, celastrol, and red ginseng extract; by tea and spice constituents, such as EGCG, epicatechin, lindenenyl acetate; and by marine products, such as eckol and fucoxanthin. p38 MAPK is also activated by fruit and vegetable constituents, such as quercetin, sulforaphane, diallyl sulfide, carnosic acid, lycopene, procyanidin B2, fisetin, and sesamin/episesamin; by herb constituents, such as Aralia continentalis extract, ginkgo biloba extract, rottlerin, celastrol, and mollugin; by tea and coffee constituents, such as EGCG and kahweol; by spices, such as curcumin and piperine; and by marine product like fucoxanthin.…”
Section: Molecular Mechanisms Of Nrf2 Activation and Dynamic Regulatimentioning
confidence: 99%